Agriculture IoT Adoption: Linking Technology Readiness, Acceptance and Entrepreneurial Ambidexterity Among Sabah Smallholders - Nurul Alam Mohd Yaakub; Viduriati Sumin; Ung Ling Ling (Research Synergy Foundation, 2026)
Internet of Things (IoT) adoption in agriculture potentially enhances operational efficiency and sustainability. However, smallholding farmers, such as in Sabah, often face barriers in terms of technological literacy, acceptance and resources. Sabah food security could be sustained through IoT-based technological interventions - therefore, it is important to investigate farmers’ readiness and acceptance towards IoT adoption. The objectives of this study are (i) to examine the influence of technology readiness on acceptance within a technology readiness-acceptance (TRAM) framework; (ii) to investigate the effects of perceived usefulness and ease of use on IoT adoption intention; and (iii) to analyse the mediating effect of entrepreneurial ambidexterity in the relationship of technology acceptance towards adoption intention among Sabahan smallholders. A quantitative research was conducted, using 385 datasets of which were analysed using partial least squares structural equation modeling (PLS-SEM) to test the research conceptual framework. Results demonstrated that (i) technology readiness motivators influence acceptance significantly, (ii) perceived usefulness emerges as the strongest predictor of adoption intention and (iii) entrepreneurial ambidexterity is a significant mediator, specifically through perceived ease of use. This study provides a novel thereotical extension of TRAM by establishing entrepreneurial ambidexterity as a mediator of IoT adoption intention. Practical directions are proposed for agricultural policymakers, technology providers and stakeholders in formulating strategies that align with farmers’ predispositions towards supporting the transformation of Sabah’s agricultural sector.